PENGARUH MODEL PEMBELAJARAN EVERYDAY MATHEMATICS DAN GAYA KOGNITIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA NEGERI 4 SELUMA BENGKULU - Galih Ageng Pambudi; Wahyu Widada; Nirwana Nirwana; Dewi Herawaty (Jupitek)
This article explains the results of research on the influence of everyday mathematics learning models on critical thinking skills of Class XI students of SMA Negeri 4 Seluma in the 2019/2020 Academic Year. This type of research is experimental research with quasi experimental. This research was conducted at SMAN 4 Seluma in the odd semester of the 2019/2020 school year with a population of all class XI and sample classes XI MIA1, XI MIA2, XI MIA3, and XI IIS2. Research data were analyzed using Ancova test. The results showed that there were differences in critical thinking skills between students taught with everyday mathematics and conventional learning models after controlling students' initial abilities with p-value = 0.00 <0.05, there were differences in critical thinking between students whose cognitive styles were Field Independent (FI), and Field Dependent (FD) cognitive style after controlling students 'initial abilities with p-value = 0.00 <0.05, there is an influence of learning model interaction and cognitive style on critical thinking skills after controlling students' initial abilities with grades p-value = 0.00 <0.05, there is a linear influence of students 'initial covariate ability on critical thinking skills with p-value = 0.00 <0.05, students' initial ability, everyday mathematics learning model and cognitive style together - the same effect on critical thinking skills p-value = 0.00 <0.05